2016
DOI: 10.4238/gmr15048873
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-4 genetic polymorphisms and environmental factors in the risk of asthma in children

Abstract: ABSTRACT. Asthma is an allergic disease characterized by hyperresponsiveness and chronic inflammation of the airway. The interleukin-4 (IL-4) gene and its single nucleotide polymorphisms are associated with asthma susceptibility in children. A case-control study was performed to evaluate the relationship between asthma risk and the IL-4 rs2243250 (589 C/T) and rs2070874 (107 T/C), and IL-4 receptor (IL-4R) rs1801275 (576 Q/R) polymorphisms in 317 childhood asthma patients and 351 healthy children as controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
5
0
3
Order By: Relevance
“…Massoud et al proposed as underlying mechanism the conversion of induced regulatory T cells toward Th17 cell inflammation driven by altered IL4R function [ 117 ]. Studies on children population reported a significant association of ILR4A polymorphisms and asthma susceptibility [ 118 ], although a more specific predisposition to asthma exacerbation risk needs to be evaluated in these patients.…”
Section: Genetic and Transcriptomic Predispositionmentioning
confidence: 99%
“…Massoud et al proposed as underlying mechanism the conversion of induced regulatory T cells toward Th17 cell inflammation driven by altered IL4R function [ 117 ]. Studies on children population reported a significant association of ILR4A polymorphisms and asthma susceptibility [ 118 ], although a more specific predisposition to asthma exacerbation risk needs to be evaluated in these patients.…”
Section: Genetic and Transcriptomic Predispositionmentioning
confidence: 99%
“…Overall, 55 studies with 9572 cases and 9881 controls included in quantitative analysis of the association between IL-4 gene -589C/T polymorphism and the risk of asthma. Of those, 11 articles were conducted in European countries [ 29 , 31 , 33 , 38 41 , 55 , 63 , 64 , 69 ], 32 articles were in Asian countries [ 27 , 30 , 32 , 34 – 37 , 43 46 , 49 , 50 , 53 , 54 , 56 – 62 , 65 , 66 , 68 , 70 – 73 ], 10 articles in American countries [ 16 , 26 , 28 , 42 , 48 , 52 ] and one article in each Algeria [ 67 ] and Australia country [ 51 ]. The analysis of overall population revealed the significant positive association between IL4 gene -589C/T polymorphism and the risk of asthma across all genetic models; including dominant model (OR = 1.22, 95% CI = 1.04–1.44, P = 0.01, REM), recessive model (OR = 1.17, 95% CI = 1.08–1.27, P < 0.001, FEM), allelic model (OR = 1.21, 95% CI = 1.09–1.33, P < 0.001, REM), and TT vs. CC model (OR = 1.34, 95% CI = 1.18–1.52, P < 0.001, FEM), except CT vs. TT model (OR = 1.13, 95% CI = 0.95–1.34, P = 0.17, REM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 Estudios anteriores indicaron que la IL-4 y su variante polimórfica de receptores aumentaban el riesgo de asma al interactuar con la exposición al humo y las mascotas. 9 La patogenia de las enfermedades alérgicas que involucran múltiples citocinas, quimiocinas y sus correlaciones analizadas como la base de la terapia de fase efectora, como anti-IgE, esteroides, miméticos β2, antagonistas del receptor de leucotrienos. 7 La IL-4 son citocinas, fundamentales y desempeñan un papel esencial en el desarrollo de la alergia.…”
Section: Introductionunclassified
“…7 La IL-4 son citocinas, fundamentales y desempeñan un papel esencial en el desarrollo de la alergia. 9 La alteración de estos genes puede dar lugar a diferentes respuestas a diversas sustancias sensibilizantes. 10 C-590 T es un polimorfismo promotor de IL-4 que influye en la transcripción de varios genes de citocinas.…”
Section: Introductionunclassified